Preparation of nanoscaled yttrium oxide by citrate precipitation method - 陈金清 黄彬 黄超 孙晓琦 (Journal of rare earths, 2017)
The nano-Y2O3 was prepared from YCl3 by the citrate precipitation method. The precursor powders were prepared by 0.1 mol/L YCl3 solution and 0.1 mol/L hydrochloric acid in the presence of 1% surfactant PEG2000, which was dried via an ethanol azeotropic distillation method. The effects of reaction temperature, precursor concentration, hydrochloric acid concentration, surfactant, and calcination temperature on the mean sizes of nano-Y2O3 were studied. It was found that the highest yield of precursor was about 70% at the p H value of 5.0, and the yield decreased rapidly at the p H value below 4 or over 6. The reaction temperature revealed no effect on the size of precursor. The optimized precursor concentration and hydrochloric acid concentration were both 0.1 mol/L. Several typical analytic techniques such as particle size analyzer, X-ray diffraction（XRD）, thermogravimetric and differential thermal analyses（TG-DTA） and scanning electron microscopy（SEM） were used to determine the characteristics of the prepared nano powders. Homogeneous torispherical nano-Y2O3 with the smallest size（20 nm） could be obtained by calcining the precursor powders at 800 oC for an hour.